Health and social conditions of elderly accompanied by primary attention in Sobral — CE - Jamilly Cruz Linhares; Eliany Nazaré Oliveira; Sara Cordeiro Eloia; Cibelly Aliny Siqueira de Lima Freitas; Hirok Shinkai; Tâmia Queiroz Lira (Rev Rene)
The demographic transition has made the aging issues gain interest, trigger studies and research and deserve worldwide distinction. The research aims to draw the profile of the social and health conditions of the elderly population accompanied by Primary Care attention in Sobral — CE, Brazil. This is an exploratory — descriptive and quantitative approach that included 200 elderly people. It was found out that 72.5% are women, 40.5% were aged between 70 and 79 years and 57% were illiterate, 61% had some kind of dependence and 48% make use of about 02 to 03 kinds of medications daily. 52% had a good family dynamics, with greater presence of the child as a caregiver. Most expressed mild depression and 34% reported good health. Thus, the data let us to conclude0020that investments that focus on disease prevention and control of chronic conditions that allow the elderly to live with a quality are required.